Effects of chronic exposure to waterborne copper and nickel in binary mixture on tissue-specific metal accumulation and reproduction in fathead minnow (Pimephales promelas). (October 2017) - Driessnack, Melissa K.; Jamwal, Ankur; Niyogi, Som
Abstract: The current study evaluated the interactive effects of chronic waterborne copper (Cu) and nickel (Ni) exposure on tissue-specific metal accumulation and reproductive performance in fathead minnow ( Pimephales promelas ). Fish trios (1 male: 2 female; n = 5–6) were exposed for 21 days to: (i) control (no added Cu or Ni), (ii) waterborne Cu (45 μg/L), (iii) waterborne Ni (270 μg/L), and (iv) binary mixture of waterborne Cu and Ni (45 and 270 μg/L, respectively). Fish fecundity (cumulative egg production) was found to be the most sensitive reproductive endpoint, and the interaction of Cu and Ni elicited an additive effect on egg production. Tissue-specific accumulation of both metals was not influenced by the interaction of Cu and Ni, except an increased Cu and Ni burden in the carcass and ovary, respectively, were recorded. The expressions of hepatic estrogen receptor genes (ER-α and ER-β) and the circulating estradiol level in females were also not affected by the metal-mixture treatment. However, co-exposure to waterborne Cu and Ni resulted in a significant downregulation of the hepatic vitellogenin gene in females, which was associated with the maximum upregulation of the hepatic metallothionein gene. In addition, a significant alteration of ovarian histopathology (decreased abundance of post-vitellogenic follicles, and increased follicular atresia) was also observed only in females exposed to Cu and Ni in mixture. Collectively, these observations suggest that chronic waterborne exposure to Cu and Ni in binary mixture may impair fish reproductive capacity by inducing histopathological damage in ovarian tissue, and disrupting of energy homeostasis in fish. Highlights: Waterborne Cu and Ni in mixture causes additive toxicity on fish reproduction. Interaction of Cu and Ni increases tissue-specific burden of both metals. Interaction of Cu and Ni downregulates hepatic vitellogenin expression. Interaction of Cu and Ni causes histopathological damage in ovary.